2012 [videorecording (DVD)] - Emmerich, Roland; Cusack, John, 1966-; Ejiofor, Chiwetel, 1977-; Peet, Amanda, 1972-; Platt, Oliver; Newton, Thandiwe, 1972-; Glover, Danny; Harrelson, Woody (Sony Pictures Home Entertainment, 2010)
A geophysical team, who are investigating the effect radiation from other solar systems has on the Earth, learn that the core of the Earth is heating up and warn the President of the United States. While the leaders of the world race to build 'arks' to escape the impending doom, volcanic eruptions and earthquakes of unprecedented strength wreak havoc all over the world.